Microplastics in seafood: Consumer preferences and valuation for mitigation technologies - Barrientos, Manuel; Vásquez Lavín, Felipe; Ponce Oliva, Roberto D.; Nayga, Rodolfo M.; Gelcich, Stefan (Food research international, 2024)
[Display omitted] •Microplastics contamination may hinder the consumption of food security essential food products.•Consumers greatly valued depuration as an emerging technology to reduce microplastics in seafood.•Information about the potential effects of microplastics impacted consumers’ preferences. Microplastics, an emerging pollutant, have garnered widespread attention due to potential repercussions on human health and the environment. Given the critical role of seafood in food security, growing concerns about microplastics might be detrimental to meeting future global food demand. This study employed a discrete choice experiment to investigate Chilean consumers’ preferences for technology aimed at mitigating microplastic levels in mussels. Using a between-subjects design with information treatments, we examined the impact of informing consumers about potential human health and environmental effects linked to microplastics pollution on their valuation for the technology. We found that the information treatments increased consumers’ willingness to pay for mussels. Specifically, consumers were willing to pay a premium of around US$ 4 for 250 g of mussel meat with a 90 % depuration efficiency certification. The provision of health impact information increased the price premium by 56 %, while the provision of environmental information increased it by 21 %. Furthermore, combined health and environmental information significantly increased the probability of non-purchasing behavior by 22.8 % and the risk perception of microplastics for human health by 5.8 %. These results emphasized the critical role of information in shaping consumer preferences and provided evidence for validating investment in research and development related to microplastic pollution mitigation measures.